Public development aid: Below the target - Volker Bethke (Intereconomics, 1973)
At the beginning of the Second Development Decade (1970–1980) the Industrial countries set themselves the target of stepping up their public development aid to 0.7 p.c. of their GNP by 1975. The validity of this aim is still emphasised by representatives of international organisations as well as spokesmen of individual industrial countries, such as the Federal Republic of Germany.
Keywords: 330; Germany